Aššur-nāṣir-apli II, King of Assyria (883-859 B.C.). With Special Reference to the Reliefs in the Brooklyn Museum - Paley, S. M.
Diss.; University Microfilms 77-259; Cf. Diss Abstr 37 (1976-77) 4523-A.